Pengetahuan dan Sikap Pedagang Ikan tentang Upaya Pencegahan Penularan Covid-19 di Pasar Kasih Kota Kupang - Damaskus Apolos Natun; Marylin Susanti Junias; Mustakim Sahdan (Media Kesehatan Masyarakat, 2021)
Coronavirus Disease 2019 (COVID-19) is a new infectious disease that has become a pandemic in all countries including Indonesia. The disease COVID-19 can be prevented by implementing health protocols recommended by the government in a disciplined manner such as wearing masks, washing hands and maintaining distance. Fish traders are one of the groups that are at risk of transmitting and spreading COVID-19 because they meet face to face with many people and the implementation of health protocols is not optimal. The purpose of this study was to describe the level of knowledge and attitudes of fish traders regarding efforts to prevent the transmission of COVID-19 in the Kasih Market, Kupang City. This type of research is descriptive with a quantitative approach. The study population was 35 fish traders and all of them were used as research subjects (total sampling). The data analysis used was univariate. The results showed that the majority of respondents had good knowledge about the prevention of COVID-19 (77.1%) and were positive about the dangers and ways of preventing COVID-19 (88.6%). Continuous education and disciplined enforcement of health protocols are needed to reduce the risk of transmitting COVID-19 in the community.